Association between polymorphism of the 5HT-2A receptor gene and vasovagal syncope - Lorenzini, Elisiane (2012)
Introduction: Vasovagal Syncope is a very frequent pathology; however, its physiopathology is not well known. Objectives: To verify the association between polymorphism T102C 5HT-2A and vasovagal syncope. Methods: This case-control study included 106 patients, selected between March 2007 and December 2008. Fifty-three patients with history of syncope and positive head-up tilt test were compared to 53 patients without history of syncope, in relation to the presence of the polymorphism. Results: Of the patients studied, 11 (22%) of the case group and 4 (8%) of the control group had familiar history in first degree of syncope (p=0.03). In the analysis of the logistic regression, the homozygote 102C (OR 4.54; IC 95%: 1.14–0.97; p= 0.02) and the familiar history (OR 2.86; IC 95%: 0.97 – 8.39; p=0.03) were independently associated to a higher chance of developing vasovagal syncope. Conclusions: Patients with familiar history of syncope and homozygote 102C have more chance of presenting vasovagal syncope.